Diversity and Correlation Analysis of Endophytes and Top Metabolites in Phlomoides rotata Roots from High-Altitude Habitats - Zuxia Li; Huichun Xie; Guigong Geng; Chongxin Yin; Xiaozhuo Wu; Jianxia Ma; Rui Su; Zirui Wang; Feng Qiao (Microorganisms)
Phlomoides rotata, a traditional medicinal plant, always grows on the Tibetan Plateau at a high altitude of 3100–5200 m. The major active ingredients in P. rotata were used in medicines due to their diverse pharmacological effects, including hemostatic, anti-inflammatory, antitumor, immuno-modulatory, and antioxidant activities. This study screened 15 top endophytic genus through the analysis of OTUs and the top 30 metabolites with relatively high content in P. rotata roots from four different habitats (HN, GL, YS, and CD regions) in Qinghai Province. Twelve physicochemical indicators were measured and analyzed in the rhizosphere soils of P. rotata habitats. The results indicated that the top 30 metabolites compounds included 7 amino acids, 5 sugars and alcohols, 4 phenylpropanoids, 3 Organic acids, and 3 Alkaloids. Four endophytic bacteria (Acidibacter, Sphingomonas, Variovorax, and Sphingobium) and three endophytic fungi (Tetracladium, Cadophora, and Minimelanolocus) were dominant genera in P. rotata roots from four habitats. There were 109 positive significant correlations and 57 negative correlations between OTUs of endophytic bacteria and contents of top 30 metabolites, and 59 positive significant correlations and 58 negative correlations between OTUs of endophytic fungus and contents of top 30 metabolites. The OTUs of Acidibacter were significantly positively correlated with the content of 5 soil physicochemical indicators (total phosphorus, amylase, sucrase, total potassium, or soil organic carbon) and significantly negatively correlated with the content of acid protease. OTUs of Tetracladium or Cadophora showed a positive correlation with the content of total phosphorus and a negative correlation with that of alkaline phosphatase. This study provides a theoretical basis for the study of the correlation between endophytes and metabolites in P. rotata roots.